(untitled) (Research, Society and Development, 2020)
The municipality of Iguatu is inserted in the South-Central Region of the State of Ceará, located in the Upper Jaguaribe hydrographic basin, with a hot and semi-arid climate, characterized by few annual rains, with two well-defined climatic seasons: rainy and dry. The analysis of rainfall series is essential in the management of water resources, in view of the influence on ecosystem processes, indispensable for the survival of species, in the transformation of geographic space and the environment, directly influencing the water balance of a region. This work aims to analyze the behavior of rainfall occurred in the municipality of Iguatu, Ceará in the period from 1974 to 2009. To carry out the research, the data were made available by the Secretary of Water Resources of Ceará (SRH) from meteorological stations of the Ceará Foundation of Meteorology and Water Resources (FUNCEME) through historical series. Statistical calculations and Kolmogorov-Smirnov test were performed using the Manitab 19 software to verify the adherence of precipitation values. From the analysis of the results, the rainy season of iguatu occurs in 4 months (January-April) and the dry period, in the rest of the year (May-December), with values below the average, reaching 230.20 mm in March and only 9.47 in November. It was found that the Kolmogorov-Smirnov test is adequate and significant for precipitation values (mm) from the probability value (P) for the study period.